Legal Harmonization of Mining Industrial Regulation: A Normative Review of Provincial Authority in Central Sulawesi, Indonesia - Syamsuddin, Adiesty Septhiany Prihatiningsih; Paskual, Meity Ferdiana; Ruslan, Ruslan (Universitas Muhammadiyah Yogyakarta, 2026)
The changes to the Mineral and Coal Mining Law in 2025 emphasize the direction of mining law policy in Indonesia, which is intertwined with the regulation of regional government authority and its development under the Job Creation Law. This research aims to explain the urgency of adjusting regional legal products related to industrialization within the framework of the Mineral and Coal Mining Law and the Job Creation Law. This analysis applies normative legal research, including statutory, conceptual, and comparative approaches. The data collection techniques used are literature and document reviews, with the results analyzed using qualitative descriptive analysis. The result indicates that the effectiveness of mining industry regulation lies in this division of affairs as a manifestation of the principle of decentralized authority of regional government. Moreover, Nawiasky and Habermas theories are used as bases for argument to emphasize the urgency of regulating aspects of industrialization at the provincial level, along with the reduction of provincial authority after the enactment of the Job Creation Law. This research concludes that the authority of the Central Sulawesi provincial government to regulate the mining industry currently requires adjustments in line with the core business of the Job Creation Law and the Mineral and Coal Mining Law. In addition, several challenges arise in the alignment process: regional autonomy and central supervision of regions, regional capacity constraints, and stakeholder involvement. These findings imply the involvement of various parties at the central and regional levels in encouraging nickel industrialization through the formulation and adjustment of laws.